Challenges in the Development of Hydropower in Selected European Countries - Paweł Tomczyk; Mirosław Wiatkowski (Proceedings, 2020)
Hydropower (HP) in Europe is playing an increasingly important role. Its share in final energy consumption varies from country to country, which is associated with different challenges for each of them. This article presents the challenges of HP development in three countries with a diversified domestic share, i.e., Albania (100% share in 2019), Slovenia (25.7%) and Estonia (0.3%). Particular attention was paid to issues of rational management of water resources in conjunction with the objectives of nature protection and European energy policy. As a result of the analysis, the following challenges in the development of HP were identified: the need to modernize the current HP network, conflicts related to the implementation of HP projects in naturally valuable areas, dependence on external electricity supply due to adverse environmental conditions, problems with the diversification of energy sources and lack of cooperation between environments representing different interests. The countries described have different local specificities; therefore, the challenges in the development of HP are different in each of them. The key to solving them is especially mutual cooperation between various environments, integration of energy markets and diversification of used energy sources, with an indication of renewable energy sources (RES). This will enable harmonious development of each country. Furthermore, it cannot be clearly determined whether the assumed objectives of EU energy policy will be achieved. Achieving these goals is possible because the share of RES in final energy consumption in the countries described is growing.